2000
DOI: 10.1007/s11745-000-0493-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of oleuropein, an olive oil biophenol, on low density lipoprotein oxidizability in rabbits

Abstract: On the basis of the results obtained with pilot studies conducted in vitro on human low density lipoprotein (LDL) and on cell cultures (Caco-2), which had indicated the ability of certain molecules present in olive oil to inhibit prooxidative processes, an in vivo study was made of laboratory rabbits fed special diets. Three different diets were prepared: a standard diet for rabbits (diet A), a standard diet for rabbits modified by the addition of 10% (w/w) extra virgin olive oil (diet B), a modified standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 47 publications
7
93
0
6
Order By: Relevance
“…We found 13 publications that addressed absorption, metabolism, or urinary excretion of olive oil phenols: five animal (Bai et al, 1998;Coni et al, 2000;D'Angelo et al, 2001;Tuck et al, 2001;Visioli et al, 2001), six human studies (Bonanome et al, 2000;Visioli et al, 2000a, b;Miro-Casas et al, 2001a, b;Vissers et al, 2002), and two studies that addressed characterisation of the metabolites of hydroxytyrosol in urine from two of the above-mentioned studies Tuck et al, 2002). One study by our group showed that apparent in vivo absorption of the ingested olive oil phenols was more than 55-66 mol% in humans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found 13 publications that addressed absorption, metabolism, or urinary excretion of olive oil phenols: five animal (Bai et al, 1998;Coni et al, 2000;D'Angelo et al, 2001;Tuck et al, 2001;Visioli et al, 2001), six human studies (Bonanome et al, 2000;Visioli et al, 2000a, b;Miro-Casas et al, 2001a, b;Vissers et al, 2002), and two studies that addressed characterisation of the metabolites of hydroxytyrosol in urine from two of the above-mentioned studies Tuck et al, 2002). One study by our group showed that apparent in vivo absorption of the ingested olive oil phenols was more than 55-66 mol% in humans.…”
Section: Resultsmentioning
confidence: 99%
“…However, Bai et al analysed hydroxytyrosol without prior deconjugation, which may cause underestimation of total hydroxytyrosol in plasma. Likewise, Coni et al (2000) also analysed olive oil phenols without deconjugation in plasma of rabbits that consumed extra virgin olive oil for 6 weeks. Thus, reliable data on plasma concentration of olive oil phenols are scarce.…”
Section: Bioavailabilitymentioning
confidence: 99%
“…Recent studies have shown the bioavailability of some phenols from wine or onions (Lapidot et al, 1998;Manach et al, 1998;Bell et al, 2000) but data on olive oil are scarce. Moreover, most of these studies have been done with rats or rabbits (Wiseman et al, 1996;Coni et al, 2000), but few with humans (Paganga & Rice-Evans, 1997;Miró -Casas et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant activity of oleuropein is mainly due to the hydroxytyrosol moiety in its structure [11]. Also oleuropein contributes to the prevention of atherosclerosis by inhibiting the oxidation of LDL and by scavenging several species that react with oxygen in the vascular wall [12,13].…”
Section: Characteristics Of Oleuropeinmentioning
confidence: 99%